Study happened pathologies in segments of electrical and hydrosanitary installations at UFVJM (Federal University of Jequitinhonha and Mucuri Valleys) - Mucuri campus (International Journal of Geoscience, Engineering and Technology, 2020)
The installations of water, sewage and energy systems arose from population's necessity in comfort and life quality, becoming crucial over the time. The term "pathology" is used in civil engineering as a way to characterise any building issues, which be caused by numerous factors. This work identify and study happened pathologies in several segments of electrical and hydrosanitary installations at UFVJM (Federal University of Jequitinhonha and Mucuri Valleys) - Mucuri campus. The analysis was based on local architectural plants, photographic and visual observations in addition to users interviews (students and university employees). From that and supported by bibliographic studies, were identified nonconformities in the facilities. In the classroom pavilion, the most critical building, around 50% area of the toilet bowls and 30% of the washbasins leaks were found, in addition to the 60% of the drains where there was no grid. In the electricity sector, all outlets were outside Brazilian standards and only 35% were in conditions of use. Considering the electrical and hydrosanitary systems importance, building influence and through the pathology amount founded at several segments in the building installations during the study, its considered important to make interventions to solve the problems encountered, because if they are poorly executed or used, these equipments and installations lose their main functions, beyond to bringing discomfort and health risks to users.